Lifestyle-related diseases following the evacuation after the Fukushima Daiichi nuclear power plant accident: a retrospective study of Kawauchi Village with long-term follow-up. Issue 7 (11th July 2016) - Ebner, Daniel K; Ohsawa, Megumi; Igari, Keiko; Harada, Kouji H; Koizumi, Akio
Abstract : Objectives: Kawauchi Village lies 20 km west of the Fukushima Daiichi nuclear power plant. On 16 March 2011, evacuation was ordered due to the threat of radiological exposure, and was lifted in April 2012. In this study, we aimed to evaluate the predisaster and postdisaster health status of the Kawauchi Villagers, measured by routine yearly physical examinations. Methods: We analysed the annual health examination data of residents of Kawauchi Village from 2008 to 2013, as available from the Japanese National Health Insurance system. Data from 2011 were not available due to the disaster. Since the health data included the same participants repeatedly from year to year, the sample was non-independent and generalised estimated equation modelling was used. A predisaster time period (2008–2010) was categorised for comparison with postdisaster 2012 and 2013. The outcome examined was the prevalence of metabolic disease, and was adjusted for confounding factors. Results: Data for 20.6%–25.9% of the total residents were available in this period. In 2013, the prevalence of metabolic syndrome (from 17.0% to 25.2%, p<0.001), diabetes (from 11.3% to 17.0%, p<0.001), dyslipidaemia (from 43.2% to 56.7%, p<0.0001), hyperuricaemia (from 5.2% to 8.4%, p=0.006) and chronic kidney disease (from 16.1% to 26.7%, p<0.001) was found to be elevated significantly compared to predisaster years, while that of obesity or hypertension did not change. Conclusions: The present follow-up study for Kawauchi Village revealed an increase in lifestyle-related disease following the March 2011 disaster and subsequent evacuation, and this trend still continues 2 years later.